2002
DOI: 10.1124/jpet.102.035220
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Clinical QT Prolongation to Outcome in the Conscious Dog Using a Beat-to-Beat QT-RR Interval Assessment

Abstract: QT interval prolongation of the electrocardiogram has been associated with the occurrence of life-threatening fatal ventricular arrhythmias. To understand the relationship between preclinical cardiac conduction assessment to clinical outcome, comparisons of free (unbound)-plasma drug concentrations and their associated effects in the conscious mongrel dog were made to the free plasma concentrations in humans reported to produce QT prolongation. E-4031 (an experimental class III antiarrhythmic), cisapride, terf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 32 publications
(28 reference statements)
2
27
0
1
Order By: Relevance
“…This question has been extensively assessed and different formulas have been proposed to correct QT values for HR in man, the best known being the formulas of Bazett (1920) and of Fridericia (1920). However, these formulas established in humans are not necessarily valid for dogs and a number of authors have proposed specific methods of correction or formulas for dogs (Van de Water et al 1989, Todt et al 1992, Matsunaga et al 1997, Spence et al 1998, Raunig et al 2001, Fossa et al 2002. In a previous publication, we have shown that none of these formulas perfectly correct the QT interval of dogs in our laboratory.…”
mentioning
confidence: 99%
“…This question has been extensively assessed and different formulas have been proposed to correct QT values for HR in man, the best known being the formulas of Bazett (1920) and of Fridericia (1920). However, these formulas established in humans are not necessarily valid for dogs and a number of authors have proposed specific methods of correction or formulas for dogs (Van de Water et al 1989, Todt et al 1992, Matsunaga et al 1997, Spence et al 1998, Raunig et al 2001, Fossa et al 2002. In a previous publication, we have shown that none of these formulas perfectly correct the QT interval of dogs in our laboratory.…”
mentioning
confidence: 99%
“…In recent years, investigators have developed other formulae to adjust the QT interval, including those involving linear regression and analysis of covariance equations (2,6,15,56,63,64). Recent reports propose that QT "correction" itself may be inappropriate and the investigators involved with these studies suggest alternate solutions (19). In the current environment, it is probably prudent to report the corrected QT interval as a well-characterized point of reference with recognition that in a few years the QTc may be of little scientific value as our understanding of this relationship develops.…”
Section: Qt Interval and In Vivo Methodologymentioning
confidence: 99%
“…Numerous correction formulae have been developed to adjust for the inverse relationship between heart rate and QT interval, although the shortcomings of these mathematical interpolations are many. Many methods of correction, and indeed noncorrection, have been proposed (2,6,15,19,56,63,64). Although the use of conscious sling-trained dogs can reduce the variability observed in the restrained animal, it is still considered preferable to utilize telemetry implants that derive cardiovascular parameters from the conscious, freeroaming animal.…”
Section: Role Of Dog-in Vivomentioning
confidence: 99%
“…This approach is highly valid because it accounts for QT variation with HR but does not assume a mathematical relationship, thus making no assumptions about the nature of the QT-HR relationship. This approach, however, requires many data points, either acquired from many, or from one individual (Davey, 2002;Fossa et al, 2002). A continuous evaluation of QT can be accomplished with a better-fitting mathematical model than the single-coefficient model.…”
Section: Methods Of Qtc Assessmentmentioning
confidence: 99%